Regulation of the Temperature-dependent Activation of Transient Receptor Potential Vanilloid 1 (TRPV1) by Phospholipids in Planar Lipid Bilayers - Sun, Xiaohui (J Biol Chem, 2015)
TRPV1 (transient receptor potential vanilloid 1) proteins are heat-activated nonselective cation channels. TRPV1 channels are polymodal in their function and exhibit multifaceted regulation with various molecular compounds. In this regard, phosphoinositides, particularly phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol 4-phosphate, are important channel regulators. However, their effects on TRPV1 channel activity have not been conclusively determined. To characterize temperature-induced activation of TRPV1 in the presence of different phospholipids, we purified the TRPV1 protein from HEK-293 cells and incorporated it into planar lipid bilayers. In the presence of 2.5 μm phosphatidylinositol 4,5-bisphosphate, TRPV1 channels demonstrated rapid activation at 33–39 °C and achieved full channel opening at 42 °C. At this temperature range, TRPV1 heat activation exhibited steep temperature dependence (temperature coefficient (Q(10)) of 18), and the channel openings were accompanied by large changes in entropy and enthalpy, suggesting a substantial conformation change. At a similar temperature range, another phosphoinositide, phosphatidylinositol 4-phosphate, also potentiated heat activation of TRPV1, but with much lower efficiency. Negatively charged phosphatidylglycerol could also induce heat activation of TRPV1 channels, although with a small-conductance state. Our data demonstrate that phospholipids, specifically phosphoinositides, are important regulators of TRPV1 and are required for heat-induced channel activity.